2020
DOI: 10.3390/electrochem1020008
|View full text |Cite
|
Sign up to set email alerts
|

Non-Precious Metal Graphene-Based Catalysts for Hydrogen Evolution Reaction

Abstract: Developing sustainable and renewable energy sources is critical as higher and higher global energy and environmental challenges arise. Hydrogen has the highest mass/energy density of any fuel and is considered one of the best sources of clean energy. Water splitting is regarded as one of the most promising solutions for hydrogen production on a large scale. Highly efficient, durable, and cost-effective catalysts for hydrogen evolution reaction (HER) are critical in the realization of this goal. Among the many … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The HER process’s thermodynamic potential is 0 V vs. NHE, making it seem like an easily achievable process. But on the contrary, the HER with very low overpotential is achieved to date mostly by a noble metal (e.g., Pt metal) as a catalyst. In the past few years, research has advanced toward betterment where a few noble metal-based materials containing a relatively less amount of Pt has shown similar results. , There are reports of bimetallic compounds that contain a certain percentage of Pt along with other metals, such as Ru/Rh, etc. Even though the results are encouraging, the catalyst’s cost is still very high for practical usage. Scientists have looked into Earth-abundant transition metal-based catalysts for the HER, taking the HER catalyst to an altogether different level.…”
Section: Introductionmentioning
confidence: 99%
“…The HER process’s thermodynamic potential is 0 V vs. NHE, making it seem like an easily achievable process. But on the contrary, the HER with very low overpotential is achieved to date mostly by a noble metal (e.g., Pt metal) as a catalyst. In the past few years, research has advanced toward betterment where a few noble metal-based materials containing a relatively less amount of Pt has shown similar results. , There are reports of bimetallic compounds that contain a certain percentage of Pt along with other metals, such as Ru/Rh, etc. Even though the results are encouraging, the catalyst’s cost is still very high for practical usage. Scientists have looked into Earth-abundant transition metal-based catalysts for the HER, taking the HER catalyst to an altogether different level.…”
Section: Introductionmentioning
confidence: 99%
“…From these processes, conglomerated carbon spherules are formed on top of a more compact multi-layer graphene-like structure. Since the laser spot scans an irregular topography, information from both the carbon spherules and the graphene support are concomitantly obtained [ 16 ]. Similar observations were also made by Li et al [ 20 ], who showed that N-doped graphene presents a curled structure.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating nitrogen atoms into the graphene structure is considered a route to creating a valance band and, consequently, to change its electronic structure [ 13 ]. Thus, it is possible to tune the electrochemical properties of nitrogen-doped graphene to synthetize a stable and highly efficient non-metallic catalyst for oxygen reduction (ORR) [ 14 ], hydrogen production (HER) [ 15 , 16 ], and oxygen production (OER) reactions [ 17 ]. Li et al [ 15 ] indicated that the free-standing N-enriched carbon foam@WS 2 nanoflakes prepared by a thermal evaporation process, can be used as the working electrodes for HER in water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…The best catalysts are the elements from the Pt group metals which are perfect from thermodynamics and kinetics point of view, but their lack and high cost hinder their large-scale use, requiring cheaper and more viable catalysts [203,204]. In this context, Luis-Sunga et al [205] recently reviewed nonprecious metal graphene-based catalysts for HER.…”
Section: Go/rgo As Electrocatalystmentioning
confidence: 99%